2021
DOI: 10.1155/2021/7475938
|View full text |Cite|
|
Sign up to set email alerts
|

Expression of Tspan8 in Patients with Intrahepatic Cholangiocarcinoma and Its Relationship with Clinicopathological Features and Prognosis

Abstract: The incidence and mortality of intrahepatic cholangiocarcinoma (ICC) are increasing worldwide. High invasion and metastasis are one of the main causes of death in patients. The selection of reasonable and effective molecular markers to evaluate the prognosis of patients with ICC has important clinical guiding significance. In this study, the expression of Tspan protein in ICC and normal tissues was compared, the correlation between Tspan expression and pathological features of patients was analyzed by the logi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%